2022
DOI: 10.3390/cancers14133095
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 Checkpoint Inhibitors Are Active in the Chicken Embryo Model and Show Antitumor Efficacy In Ovo

Abstract: (1) Purpose: To assess the use of the chicken embryo (in ovo) model as an alternative in vivo model for immuno-oncology (IO) drug development, focusing on programmed cell death protein-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) immune checkpoint inhibitors. (2) Methods: First, the presence of immune cells in the model was detected through the immunophenotyping of chicken peripheral blood mononuclear cells (PBMCs) based on fluorescence activated cell sorting (FACS) analysis and the immunohistochemistry (IH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
(52 reference statements)
2
6
0
Order By: Relevance
“…Here, human monocyte-derived dendritic cells isolated from healthy donors were engrafted 1:1 with the immortalized tumor cell lines and grown on the CAM for 7 days. Reduction in tumor burden correlated well with results obtained in a model of peritoneal (75). However, appropriate controls and quantification of crucial mechanistic insights, including checkpoint antibody binding assays, were largely missing, questioning the scientific relevance of such findings.…”
Section: Addressing Cancer Immunity In Ovosupporting
confidence: 58%
See 2 more Smart Citations
“…Here, human monocyte-derived dendritic cells isolated from healthy donors were engrafted 1:1 with the immortalized tumor cell lines and grown on the CAM for 7 days. Reduction in tumor burden correlated well with results obtained in a model of peritoneal (75). However, appropriate controls and quantification of crucial mechanistic insights, including checkpoint antibody binding assays, were largely missing, questioning the scientific relevance of such findings.…”
Section: Addressing Cancer Immunity In Ovosupporting
confidence: 58%
“…A widely different approach was employed by Wang and colleagues, who took advantage of homologies in the PD1/PDL1 axis between chickens and humans and proposed the TUM-CAM model as an alternative for immunooncological drug development. Clinically approved checkpoint inhibitors mitigated tumor growth in ovo and partially restored T cell-mediated tumor toxicity of chicken lymphocytes in vitro ( 75 ). However, appropriate controls and quantification of crucial mechanistic insights, including checkpoint antibody binding assays, were largely missing, questioning the scientific relevance of such findings.…”
Section: Aspects In Cancer Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…Animal protocol approvals are not required for the use of the CAM model (country-dependent). Moreover, being naturally immunodeficient until embryonic day (ED) 10, transplantations from different tissues and species may be performed with only minor immune responses, whereas at ED16, cytotoxic T cells and monocyte populations are available [ 78 ]. Furthermore, in contrast to the CAM model, murine in vivo models allow for a longer observation time.…”
Section: Discussionmentioning
confidence: 99%
“…At EDD18, i.e., 9 days post-graft, in ovo anti-tumor efficacy was evaluated by tumor weight, metastatic invasion (qPCR analysis of human Alu sequence in lower CAM) and quantification of tumor-infiltrating by CD8, CD4, IFN-gamma, Perforin and TNF-alpha. 1,2 Results Compared to negative control, STC-1010 vaccine induced: 1) significant increase of IL-12 and IL-2 secretion in peripheric blood during the generation of all three batches of PBMCs, confirming previous results (IL-12: +52%, p=0.0003 ; IL-2: +482%, p=0.0033); 2) a significant expression of IFN-gamma in tumor (+130,83%, p=0.0185); 3) a tendency to increase infiltrating cells: CD4+: +79,2%, CD8+: +29,4% , Perforin: +105,5%, TNFa : +78,63% confirmed by immunohistochemistry and translated into 4) a significant increase of tumor necrosis (p = 0.0267); and 5) a tendency of metastasis regression (-49%); with 6) no embryonic toxicity/mortality (daily evaluation of embryonic viability) induced by STC-1010. Conclusions This in ovo study confirms efficacy of the STC-1010 observed in previous CRC syngeneic models and gives more insight about STC mechanism of action with the activation and maturation of dendritic cells, induction of CD8+ and LTh1 against tumor as the main driver of the response, all without toxicity.…”
mentioning
confidence: 99%